Effects of Distance Learning on the Academic Performance of Selected Tourism Students of Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Distance learning relies on the educational tools of online learning, making it more accessible for students. It is also known to be more affordable, another factor that helps make education more accessible to many students at different socio-economic levels. Many educational institutions can now implement distance learning to ensure the availability of educational resources and services. This research study aims to know the effects of the distance learning approach on the academic performance of selected tourism students in Bestlink College of the Philippines. This study aimed to see how demographic factors affect academic performance. The researchers conducted the study using the descriptive survey method to accumulate answers on the effect of distance learning on the academic performance of selected tourism students.   This study is descriptive research because descriptive research is used to describe population or individual characteristics. It does not explain how, when, or why the features developed. The study focuses on the Effects of the Distance Learning approach on the Academic Performance of selected tourism students. This study aims to determine the Effects of the Distance Learning Approach on the Academic Performance of Selected fifty (50) Tourism Students at Bestlink College of the Philippines who are officially enrolled during the Academic Year 2022-2023. This study utilized the cluster random sampling technique. According to Frey (2018), cluster sampling is a probability sampling technique in which all population elements are categorized into mutually exclusive and exhaustive groups called clusters.  The researchers will select fifty (50) Tourism Students in Bestlink College of the Philippines who are officially enrolled during the Academic Year 2022-2023. The researchers made the survey questionnaire. It was used in the gathering of data and information in the study. The survey questionnaire is necessary for the study. The survey questionnaire includes objectives, scope/content, instructional materials, strategies, and evaluation for organizing a webinar.